Investigations of the Class I methanol masers in NGC 4945. Issue 4 (9th August 2018) - McCarthy, T P; Ellingsen, S P; Breen, S L; Henkel, C; Voronkov, M A; Chen, X
ABSTRACT: We have used the Australia Telescope Compact Array (ATCA) to conduct further observations of the 36.2-GHz (4−1 → 30 E) methanol transition towards the nearby active galaxy NGC 4945. These observations have led to a more accurate determination of the offset between the maser emission and the nucleus of NGC 4945 with a typical synthesized beam of 6 arcsec × 4 arcsec (108 × 72 pc). This corresponds to a factor of 4 improvement with respect to the major axis of the beam. Other transitions of methanol and lines of other molecular species were obtained alongside the 36.2-GHz methanol emission, with strong detections of HC3 N (J = 4 → 3) and CS (J = 1 → 0) presented here. We do not detect thermal methanol (5σ upper limit of 5 mJy in a 6 km s −1 channel) from the 48.4-GHz (10 → 00 A + ) ground-state transition, nor emission from the 44.1-GHz (70 → 61 A + ) class I maser transition (5σ upper limit of 6 mJy in a 3 km s −1 channel). We also present a comparison of the class I maser emission observed towards NGC 4945 with that from NGC 253 and towards the Galactic giant molecular cloud G 1.6-0.025.